Data from: Reduced representation sequencing reveals weak genetic differentiation between Canadian and European Larus hyperboreus (Glaucous Gull) ... - Lachance Linklater, Emma; Sonsthagen, Sarah A.; Robertson, Gregory J.; Colston-Nepali, Lila; Vigfúsdóttir, Freydís; Friesen, Vicki L. (Dryad, 2025)
Climate change poses a significant threat to Arctic ecosystems. Evaluation of genetic diversity within and differentiation among populations is needed to effectively conserve Arctic species and ensure genetic variation is appropriately managed. This research examined population genetic structure in Larus hyperboreus (Glaucous Gull), a circumpolar Arctic species that is declining in parts of its range. Population genetic information is needed to help delineate management units, including information on genetic differences among related species, among subspecies (currently distinguished by subtle morphometric and plumage differences), and among colonies in North America. We conducted double-digest restriction site-associated DNA sequencing for 62 L. hyperboreus, 18 L. argentatus smithsonianus (American Herring Gull), 6 L. a. argentatus (European Herring Gull), and 15 L. glaucescens (Glaucous-winged Gull) sampled across the Canadian and European Arctic. Interspecific analyses using 2,145 loci were unable to ... : # Data from: Reduced representation sequencing reveals weak genetic differentiation between Canadian and European Larus hyperboreus (Glaucous Gull) ## Description of the data and file structure: SNP data was obtained from ddRAD sequencing ## File contents: ## trial2_sp.st STRUCTURE file containing 98 individuals. Species identity when sampled in the field is given in column 2 with 1 denoting Glaucous Gull, 2 denoting European Herring Gull, 3 denoting American Herring Gull, and 4 denoting Glaucous-winged Gull. Sampling location for each individual can be found in supplemental materials. ## Trial1.st STRUCTURE file containing 62 individuals sampled in the field as Glaucous Gulls. Sampling location for each individual can be found in supplemental materials. ## nohybs_baff.st STRUCTURE file containing 56 Glaucous Gull individuals. Through analysis, we came to question the species identity of some of the sampled birds in Trial1.st and trial2_sp.st. To create this file, any individual believed to be a hybrid or ...